Oxford reading tree: The lost teddy - Roderick Hunt (Karachi; Oxford University Press, 2012)
The Stage 1 Biff, Chip and Kipper Stories provide both wordless stories and a rich story context to help develop language comprehension and decoding skills with simple first words and sentences. Wordless Stories A introduce the characters and children learn that the pictures tell a story
Keywords: Readers (Elementary)